Social Embeddedness of Firefighters, Paramedics, Specialized Nurses, Police Officers, and Military Personnel: Systematic Review in Relation to the Risk of Traumatization - Geuzinge, Renate; Visse, Merel; Duyndam, Joachim; Vermetten, Eric (Frontiers in Psychiatry, 2020)
Background Firefighters, paramedics, specialized nurses working in Intensive Care Units (ICUs), Operating Rooms (OR) and Emergency Rooms (ER), police officers and military personnel are more frequently exposed to potentially traumatic events than the general population; they are considered high-risk professionals. To reduce the risk of traumatization it is of great importance to be embedded in a social environment with supportive relationships. Methods We performed a systematic review (based on the PRISMA-Guidelines) looking for social connections within the environment in which high-risk professionals are embedded (work, home, community), to obtain evidence on the impact of these connections on the risk of traumatization. Additionally, we aim to identify relevant supportive relationships in the professionals’ environments. We identified the relevant scientific literature by searching, without time restriction, five electronic bibliographic databases: MEDLINE, PsycINFO, Sociological Abstracts, CINAHL, and Web of Science. These databases were last searched in January 2019. Results A qualitative analysis of the 89 eligible (out of 9,047 screened) studies shows that for firefighters, paramedics, and emergency nurses social connections in their work environment are predominantly supportive relationships and may protect them against traumatization. In other occupations (OR-nurses, ICU-nurses, police officers), however, social connections at work are not only a source of support but are also a source of stress. For military personnel study results are inconclusive as to whether their social connections at work or at home support them against traumatization. In so far as connections are supportive, their sources vary greatly from one occupational group to another; they differ between work versus home as well as within work between peers versus supervisor. Conclusions Being embedded in a social environment, i.e. having social connections, is important but not always sufficient to protect high-risk professionals against traumatization. For, while these connections may be the antecedents of supportive relationships, they can also be the antecedents of damaging relationships. Additionally, the sources of supportive relationships differ among groups. This suggest that knowledge of how the social structures of the occupational groups differ may increase our understanding of the impact of social connections and relationships, including socialization, on the risk of traumatization of high-risk professionals.